Moderate and Severe Blood Pressure Elevation Associated with Stroke in the Mexican Hispanic Population - Senior, Derek (Health (Irvine Calif), 2017)
BACKGROUND: Stroke is the fourth leading cause of death in US. Amongst other factors such as age, sex, race, genetics, obesity, diabetes etc., hypertension continues to be the leading contributing factor towards stroke. Studies regarding stroke in Hispanics are sparse and inconclusive. OBJECTIVES: The objective of the present study is to investigate the potential association between blood pressure elevation and risk of ischemic stroke among the Mexican Hispanic population. METHODS: A retrospective data analysis was carried out for a planned case-control study with case-control ratios of 1:2. Mexican Hispanic cases were from the ElPasoStroke database with diagnosed hypertension that had sustained an ischemic stroke (n = 505) and Mexican Hispanics diagnosed with hypertension who were stroke-free as controls from the 2005–2010 NHANES databases (n = 1010). In this analysis, we included subjects who had data on systolic, diastolic or mean arterial blood pressures for cases (327) and controls (772). In cases, blood pressure was determined by the initial admission measurement, and in controls, the first measured blood pressure was used. The unadjusted and adjusted effects of continuous measurements of systolic, diastolic and mean arterial blood pressure on stroke were determined using logistic regression analyses. Subjects were further classified into groups based on prehypertension and hypertension ranges, as established by the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7). Unadjusted and adjusted logistic regression models were also used to determine the effect of categorized blood pressures. RESULTS: Our data indicate that per unit increase in systolic, diastolic or mean arterial blood pressure elevates the odds of stroke among the Mexican Hispanic population. Adjusted analysis of categorized blood pressures showed that mild or moderate/severe high blood pressure significantly associated with odds of stroke. Maintaining and controlling blood pressure at more stringent and lower levels, specifically lowering mean arterial pressure may effectively reduce the odds of ischemic stroke among the Mexican Hispanic population. CONCLUSION: Elevation of blood pressure increases the odds of stroke among the Mexican Hispanic population. Our results provide new strategies to manage the stroke prevention and health disparity issues among the Mexican Hispanic population.